Coronoid Head And Neck Height On Left Side Of The Mandible Using Orthopantomogram For Gender Determination. - R Nair, Vedha; Anand M, Vijay (Journal of Neonatal Surgery, 2024)
INTRODUCTION:Coronoid process can be an admirable graft for maxillofacial reconstructive surgeries. The mandibular coronoid process is derived from a Greek word ‘korone’ and described as a triangular piece of flattened bone which projects upwards from the anterior part of the mandibular ramus. However it exists in various shapes and sizes. Coronoid morphology and clinical and other applications in reconstructive surgery and anthropology have been thoroughly established in the literature. Maxillofacial surgeons can use knowledge of the coronoid process's various morphological forms during reconstructive procedures and as a donor site for sinus augmentation. It is also useful in anthropological studies and in forensic dentistry. This study focuses on the determination of the various coronoid process head and neck height on the left side and its correlation with age and sex estimation. MATERIALS AND METHOD:For the study, 30 Orthopantomogram of 15 male and 15 female were obtained from Saveetha Dental College and Hospitals who underwent examination for several reasons at the university dental radiology and imaging clinic. After obtaining the height of the coronoid processes statistical analysis was performed using SPSS version 23. RESULT:The coronoid head and neck height for males were obtained as 3.69 +1.93 and for females as 5.70+1.44. CONCLUSION: The coronoid process on the right side was more dimorphic in nature than the left side. Hence, the coronoid process can serve as an important anthropometric measurement for identification....